Use of Polymer-Supported 4-(N,N-Dimethylamino)pyridine in a Formal Conjugate Addition/Elimination Mediated by an N-Ylide Generated In Situ for the Construction of Highly Functionalized Itaconimides/Alkenes - Saha, Suman K.; Jain, Anshul; Kumari, Akanksha; Bhutia, Tshering Sangmo; Agrawat, Chanchal; Rana, Nirmal K. (Synlett, 2022)
A simple, mild, and metal-free cascade reaction has been developed for the construction of highly functionalized olefins. The approach relies on the initial formation of [3+2]-cycloadducts from a pyridinium ylide generated in situ from polymer-bound DMAP (PS-DMAP) with an N-substituted maleimide or an α,β-unsaturated β-keto ester. The cycloadduct decomposes to regenerate supported DMAP and yield a functionalized itaconimide or olefin. The method has a broad substrate scope. The alkene product has been further transformed into trisubstituted furan. PS-DMAP could be reused for five cycles.
Keywords: dimethylaminopyridine; heterogeneous catalysis; ylides; cycloaddition; itaconimides; alkenes